The Lost Art of Using Bull’s Eye Lamp and Head Mirror in ENT Practice - Dr. G. Siva Prasad; Dr. Thurumella Madhulika Rathan; Dr. C. Arun Kumar; Dr. T. Chandra Kala; Dr.V. Praisy Sharon (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: To explore the historical significance, clinical utility, and potential resurgence of the bull’s eye lamp and head mirror in modern ENT practice. Methods: A review of historical literature combined with a survey of current ENT practitioners regarding their knowledge and use of these traditional tools. Results: The bull’s eye lamp and head mirror were once indispensable tools in ENT practice, offering unique advantages in terms of simplicity, cost-effectiveness, and precision. While largely supplanted by modern technology, they still hold educational and practical value in specific clinical settings. Conclusion: Reintegrating the bull’s eye lamp and head mirror into contemporary ENT practice could enhance clinical skills and offer cost-effective solutions, particularly in resource-limited settings.